PERLINDUNGAN HUKUM KLIEN NOTARIS AKIBAT PENYALAHGUNAAN DATA PRIBADI OLEH FREELANCE - Fahmi Nugraha; Rosalinda Elsina Latumahina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Notary as a public official who is given authority by the government in terms of making authentic deeds and is responsible for making authentic deeds to guarantee legal certainty in carrying out an agreement. In carrying out its authority, a Notary requires the assistance of a workforce that can be called a Notary's employee or staff. Because a Notary must be careful in carrying out his services because the negligence, he makes can cause legal problems in the future so that the Notary can be confronted in court proceedings. However, apart from notary employees who work within the scope of the notary's own office, there are also freelancers who also assist the notary in completing the obligations and authorities as a notary. Not bound by work agreements with freelancers, it will be difficult for a notary to supervise freelancers in carrying out their duties. By bringing important documents of Notary clients, these freelancers are very easy to misuse them. In the current era of technological advances, personal data is vulnerable to misuse by only using the internet, even though personal data is true and real personal information and is inherent in a person. In this study, the authors use a type of normative legal research. Normative legal research is legal research conducted by examining literature or secondary data. The results of the study show that the legal relationship between a notary and a freelancer is the existence of a power of attorney given over the files delegated to the freelancer. In Article 1797 of the Civil law, it is also explained that the recipient of the power of attorney is not allowed to do something that goes beyond his power. He can only exercise the power given to complete an interest. For this reason, it can be noted that the granting of this power only covers management limits. The protection of notary clients due to misuse of personal data by freelancers is entirely the responsibility of the freelancers themselves because they have exceeded what has been authorized